Investigating E-Banking Service Quality in Islamic Banking: A Moderated Mediation Approach - Defi Insani Saibil (Ekonomi Syariah IAIN Kudus, 2023)
The main objective of this study is to analyze the relationship between the quality of e-banking services and customer loyalty through e-satisfaction. It also aims to consider the role of self-efficacy as moderation from the perspective of internet banking and mobile banking in Islamic banking. This study employs WebQualTM and E-S-Qual as a measurement scale for e-banking service quality. In addition, the study also utilizes the moderated mediation approach to verifying the variables that influence customer loyalty in the context of Islamic banking e-platforms. Empirically, the findings show that self-efficacy, when operating as a moderator, has a considerable impact on the nexus between e-banking service quality and customer loyalty via e-satisfaction. This study also provides several theoretical contributions to the existing literature that underline the insight into loyalty, e-banking service quality, and customer psychological characteristics.